Comparing hospital and telephone follow-up after treatment for breast cancer: randomised equivalence trial. (14th January 2009) - Beaver, Kinta; Tysver-Robinson, Debbie; Campbell, Malcolm; Twomey, Mary; Williamson, Susan; Hindley, Andrew; Susnerwala, Shabbir; Dunn, Graham; Luker, Karen
Abstract : Objective To compare traditional hospital follow-up with telephone follow-up by specialist nurses after treatment for breast cancer. Design A two centre randomised equivalence trial in which women remained in the study for a mean of 24 months. Setting Outpatient clinics in two NHS hospital trusts in the north west of England Participants 374 women treated for breast cancer who were at low to moderate risk of recurrence. Interventions Participants were randomised to traditional hospital follow-up (consultation, clinical examination, and mammography as per hospital policy) or telephone follow-up by specialist nurses (consultation with structured intervention and mammography according to hospital policy). Main outcome measures Psychological morbidity (state-trait anxiety inventory, general health questionnaire (GHQ-12)), participants' needs for information, participants' satisfaction, clinical investigations ordered, and time to detection of recurrent disease. Results The 95% confidence interval for difference in mean state-trait scores adjusted for treatment received (−3.33 to 2.07) was within the predefined equivalence region (−3.5 to 3.5). The women in the telephone group were no more anxious as a result of foregoing clinic examinations and face-to-face consultations and reported higher levels of satisfaction than those attending hospital clinics (intention to treat P<0.001). The numbers of clinical investigations ordered did not differ between groups. Recurrences were few (4.5%), with no differences between groups for time to detection (median 60.5 (range 37-131) days in hospital group v 39.0 (10-152) days in telephone group; P=0.228). Conclusions Telephone follow-up was well received by participants, with no physical or psychological disadvantage. It is suitable for women at low to moderate risk of recurrence and those with long travelling distances or mobility problems and decreases the burden on busy hospital clinics. Trial registration National Cancer Research Institute 1477.